2D MoS2 Heterostructures on Epitaxial and Self‐Standing Graphene for Energy Storage: From Growth Mechanism to Application. Issue 4 (13th October 2021) - Zebardastan, Negar; Bradford, Jonathan; Gupta, Bharati; Lipton‐Duffin, Josh; MacLeod, Jennifer; Pham, Hong Duc; Dubal, Deepak; Ostrikov, Kostya; Wolff, Annalena; Hu, Kailong; Ito, Yoshikazu; Mariani, Carlo; et al.
Abstract: Layered molybdenum disulphide (MoS2 ) crystals in combination with graphene create the opportunity for the development of heterostructures with tailored surface and structural properties for energy storage applications. Herein, 2D heterostructures are developed by growing MoS2 on epitaxial and self‐standing nanoporous graphene (NPG) using chemical vapor deposition (CVD). The effect of substrate as well as different CVD growth parameters such as temperature, amount of sulfur and MoO3 precursors, and argon flow on the growth of MoS2 is systematically investigated. Interestingly, various structures of MoS2 such as monolayer triangular islands, spirals, standing sheets, and irregular stacked multilayered MoS2 are successfully developed. The growth mechanism is proposed using different advanced characterization techniques. The formation of a continuous wetting layer with grain boundaries over the surface prior to formation of any other structures is detected. As a proof of principle, MoS2 /NPG is employed for the first time as anode material in potassium ion battery. The electrode delivers a specific capacity of 389 mAh g −1 with over 98% stability after 200 cycles. The porous structures clearly facilitate the ion transport which is beneficial for the ion battery. These encouraging results open new opportunities to develop hierarchical heterostructures of 2D‐materials for next‐generation energy storage technologies. Abstract : The growth mechanism of MoS2 on different graphene substrates, including epitaxial graphene on SiC and self‐standing graphene sponge, with excellent control of the epitaxy allowing to generate both flat islands and vertically standing flakes, is investigated. Samples of MoS2 with the latter morphology on graphene sponge are used as an advanced anode material for K‐ion batteries with record charge storage.